Genetic diversity of dourado used in stock enhancement programs in the Paranapanema River - Gomes, Patrícia Cristina; Pereira Ribeiro, Ricardo; Sirol, Rodolfo Nardez; Lopera-Barbosa, Nelson Maurício; Moreira, Heden Luiz Marques; Pohv, Jayme Aparecido; Mangolin, Claudete Aparecida; Vargas, Lauro; Jacometo, Carolina Bespalhok; Streit Júnior, Danilo Pedro (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to estimate by RAPD markers the genetic diversity of a Salminus brasiliensis lot used in stock enhancement programs in the Paranapanema River, Paraná, Brazil. Ten broodstocks (five males and five females) and their progeny (40 larvae and 40 fingerlings) were analyzed. Eight analyzed primers produced 96 fragments, of which 81.2% were polymorphic. There was significant difference in the frequency of 32 out of the 96 fragments, with the presence of an exclusive fragment in the fingerlings. The Shannon index, the percentage of polymorphic fragments, and the genetic distance and identity showed less genetic divergence between broodstocks and larvae, besides a decrease of genetic variability in the fingerlings. Genetic divergence was lower in the fingerlings in comparison to the larvae and broodstocks. The molecular variance results showed that most of the genetic variation is within (90.05%) and not between groups (9.95%). The broodstock lot has high genetic variability, and genetic differences were observed between the larval and fingerling stages.